AL-QUR’AN READING SKILL AND ARABIC WRITTEN ABILITY OF STEI PERMATA STUDENTS - Siti Imaniatul Muflihatin (STAI Al-Hidayat Lasem, 2024)
As well as the influence of the ability to read the Koran on the ability to writeArabic. The results showed that the ability to read the Koran had an average valueof 74.03. 43.75% of the total respondents got a low score, 53.125% got a highscore, and 3.125% were moderately addicted. While the ability to write Arabic theaverage value obtained is 77.31. The low category is 18.75%, medium; 21.875%,and as high as 59.375%. As for the effect of literacy in reading the Koran on theability to write Arabic, it obtained a value of R-table < R-count, namely 0.063 <4.00, meaning that Ha was accepted and Ho was rejected which stated that therewas an influence between literacy in reading the Koran and the ability to writeArabic in students of STEI Permata